Building Cultural Independence Through Charismatic Leadership in Islamic Boarding Schools - Babussalam, Babussalam; Mashudi, Mashudi; Rodliyah, St (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to explore the role of charismatic leadership in fostering cultural independence within Islamic boarding schools (pesantren), with a specific focus on Pondok Pesantren Nahdlatut Tholibin Blado Wetan in Probolinggo, Indonesia, under the leadership of KH. Ahsin Ahsanakallah. Islamic boarding schools are crucial in preserving cultural and religious values while adapting to modern challenges; however, their leadership often faces difficulties in balancing tradition and innovation. Using a qualitative case study approach, data were collected through semi-structured interviews with kiai, teachers, and students; participant observation; focus group discussions; and document analysis of pesantren archives and related literature. The data sources combine primary information from internal stakeholders and secondary materials from religious manuscripts and institutional documents. The analysis employed the Miles and Huberman model, consisting of data reduction, data display, and verification, complemented by triangulation to ensure validity. The research findings reveal that Kiai's leadership serves as a central figure in preserving the culture of the Islamic boarding school and guiding the students towards cultural independence. The study highlights that his leadership strategies, including internalising cultural values and mobilising community participation, strengthen the cultural autonomy of the Islamic boarding school. The Kiai acts as a